Application of CaO-based/Au nanoparticles as heterogeneous nanocatalysts in biodiesel production. (15th January 2016) - Bet-Moushoul, Elsie; Farhadi, Khalil; Mansourpanah, Yaghoub; Nikbakht, Ali Mohammad; Molaei, Rahim; Forough, Mehrdad
Highlights: The CaO–AuNPs were used in transesterification of sunflower oil to biodiesel. The prepared CaO–AuNPs nanocatalysts exhibited superior catalytic activity. The conversion under optimized conditions was 90–97%. The catalyst was reused 10 times without significant loss of activity. The glycerol amount in the final products was very low. Abstract: In this work, five different types of calcium oxide-based catalysts supported gold nanoparticles (AuNPs) (named as nanocatalyst), including commercial CaO, egg shell, mussel shell, calcite, and dolomite were prepared and used in biodiesel synthesis. The optimal conditions of transesterification process were observed at 65 °C with a methanol to oil molar ratio of 9:1, a reaction time of 3 h and a catalyst loading of 3%. Under optimum conditions, the oil conversion was in the range of 90–97% and the glycerol amount was from 3.9 to 4.3 (mg/kg) for all samples. Gas chromatographic analysis showed that a high quality biodiesel product was synthesized using supported AuNPs catalysts in comparison with conventional CaO catalysts. Reusability results showed that all prepared nanocatalysts were able to be reemployed up to 10 times without loss of activity. It was found that CaO–AuNPs nanocatalysts prepared by impregnation method rendered them the higher catalytic activity.